PENERAPAN MEDIA PEMBELAJARAN BERBASIS VIDEO UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN IPAS MATERI SISTEM PERNAFASAN PADA MANUSIA DI KELAS V UPT SD NEGERI 173328 PANGASEAN - Tarigan, Juniko Esra; Manalu, Petronella Sionang Siska (Unversitas Katolik Santo Thomas, 2025)
This study is driven by the urgent need for expertise in teaching possessed by a teacher, models and methods used and accurate for learning activities, and media chosen for successful and comfortable teaching and learning activities. The purpose of this study is to provide a description of the process of implementing video-based learning media in learning for fifth grade elementary school students in the subject of science and its influence. In this research activity, the type of research used is qualitative descriptive research. The three main methods of data collection are interviews, observation, and documentation. Data reduction, presentation, and drawing conclusions are techniques used in analyzing data. The source of information or learning participants in this study came from students at the UPT SD Negeri Pangasean school, especially class V. In the research conducted, it was found that the application of video-based learning media as a medium effectively had a positive effect. RPP, compilation of material suitability with the competencies to be achieved, editing video-based learning media, and searching for video visualizations on YouTube are examples of learning activities. The positive impact on learning motivation resulting from the application of video-based learning media during the learning process with an average score of 81.67 with the Very Good category. This study suggests that policy makers of institutions or institutions assist teachers in obtaining video tools or media so that teachers can be creative and students can be more serious and focused in learning.